Liquid platelet-rich fibrin produced via horizontal centrifugation decreases the inflammatory response and promotes chondrocyte regeneration in vitro - Li, Huimin; Xia, Ting; Zeng, Hao; Qiu, Yun; Wei, Yan; Cheng, Yihong; Wang, Yulan; Zhang, Xiaoxin; Ke, Jin; Miron, Richard; He, Qing (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Recently, liquid platelet-rich fibrin (PRF), a rich source of concentrated platelets and growth factors, has emerged as a promising agent for stimulating tissue regeneration. However, its specific efficacy in chondrocyte proliferation and cartilage regeneration remains underexplored. To address this question, we investigated liquid PRF obtained through horizontal centrifugation and compared its effects with hyaluronic acid (HA), a high molecular weight glucosamine supplement widely used in clinical practice to safeguard against chondral damage.Liquid PRF, produced using horizontal centrifugation (liquid H-PRF) at 500 g for 8 minutes, served as our experimental agent. We conducted cell viability and proliferation assays using PRF-conditioned medium. We assessed the chondrocyte phenotype of ATDC5 cells through toluidine blue and alcian blue staining, real-time polymerase chain reaction (RT-PCR), Western blotting, and immunofluorescence staining. Furthermore, we examined the expression of genes involved in inflammation through RT-PCR and Western blot analysis.Results: Liquid H-PRF exerted notable effects on chondrocytes, influencing proliferation, inflammatory responses, and chondrogenic differentiation. The H-PRF group displayed significantly higher expression of chondrogenic markers, including Col2a1, compared to HA-treated cells, whereas aggrecan expression was significantly higher in the HA group. PRF also demonstrated the ability to reduce inflammatory levels in chondrogenic ATDC5 cells, and this effect was further enhanced when PRF from the buffy coat zone was added. In comparison, chondrocytes cultured in the HA group produced significantly fewer inflammatory factors than those in the PRF group, as confirmed qualitatively by Western blot analysis.Conclusions: Liquid H-PRF emerged as a potent stimulator for chondrogenesis and a regulator of the inflammatory response, achieving levels similar to HA. Moreover, liquid H-PRF exhibited strong potential for enhancing the production of cartilage extracellular matrix and promoting chondrogenic regeneration with notably increased Col2a1 levels. Future research should encompass animal studies and human trials to further evaluate the comparative effectiveness of liquid PRF versus HA, potentially as an alternative or complementary strategy for future clinical applications.